Analysis of the performance of high school seniors in college admissions tests and its implications to secondary education - Anacleto, Mary Anne Cabe 1950- (1987)
The aim of the study is to determine the difference in the scholastic aptitude of high school seniors during a five-year span using the NCEE and CSAT scores taken nationwide. It also seeks to determine the factors that can affect regional variation and to test the difference in school performance with schools classified according to location, type, and status. The study tries to establish if a trend in scores existed and if the scores are affected by family income. Results of the study have implications on secondary education in the Philippines. The strengths and weaknesses of the outcomes of secondary education can be identified and these can be utilized by the policy-makers in the Department of Education Culture and Sports to improve secondary education in the country.
Thesis (Ph.D.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Universities and colleges -- Entrance examinations; Academic achievement -- Testing; National College Entrance Examination